Pampanga lantern industry: funding needs, sources and interventions - Valerio, Elisha Jeshurun B.; Bronola, Dianne Katrina; Galang, Bernadette Ann; Jimenez, Marianne Danette D.; Pante, Maria Angelica; Tanaka, Reejane; Cardenas, Jerush Ann; Melencio, Kayluck; Pabelico, Sarah Mae Aiko P.; Serrano, Enna Amor
Lantern making is a major industry in Pampanga. Many small-scale businesses of this industry have sprouted in the area of San Fernando, and most of these businesses were established many years ago. Despite being around for many years, these small-scale businesses were not able to expand rapidly in terms of their size of production since access to needed capital is limited. However, capital intervention is possible as the City of San Fernando has a large pool of financial intermediaries willing to offer business loans to the lantern-makers.